Progression of Voice and Speech Impairment in the Course of Parkinson's Disease: A Longitudinal Study - S. Skodda; W. Grönheit; N. Mancinelli; U. Schlegel (Parkinson's Disease)
Impairment of voice and speech occurs in the majority of patients in the course of Parkinson's disease (PD). The aim of the current study was to survey the changes of voice and speech performance in the individual patients over time. 80 patients with PD and 60 healthy speakers were tested and retested after at least 12 months (average time interval: 32.5 months). Participants had to read a given text which was digitally recorded as a source for the perceptual and acoustic analysis. Stage of the disease and global motor impairment were rated according to the accepted scales. As a result, abnormalities of voice and speech were already present in mildly affected patients and there were significant deteriorations of quality of voice and articulatory velocity and precision between baseline and followup examination which showed no correlation with the time interval between the visits. Summarized, voice, and speech performance were found to further deteriorate in the individual patient in the course of time although global motor impairment was widely stable which might be a hint for nondopaminergic mechanisms of progression of dysarthrophonia. Further investigations are warranted to get a better insight into the dynamics of the progression of voice and speech impairment in PD as a precondition for the development of therapeutic approaches.